Textiles. (1st October 2017) - Choudri, B.S.; Charabi, Yassine; Baawain, Mahad; Ahmed, Mushtaque
Abstract : A review of the literature published in 2016 on topics relating to the treatment alternatives for wastewater from the textile industries is presented. This review is divided into the following sections: a brief introduction on the implementation of the Best Available Techniques into textile industry, a review of the more promising treatment technologies distinguished into physico‐chemical, biological and combined processes.